THE ROLE AND OPPORTUNITIES OF DIGITAL TECHNOLOGIES IN INCLUSIVE EDUCATION - Safieva Mokhinur Akramkizi (Modern American Journals, 2025)
This article examines the role and opportunities of digital technologies in the development and support of inclusive education. The focus is placed on how digital tools can create more equitable learning environments for children with special educational needs by providing flexibility, accessibility, and individualized learning experiences. Modern digital platforms, assistive technologies, and interactive resources have transformed the educational process, enabling teachers to design inclusive classrooms that respond to diverse needs. In particular, the paper highlights the significance of adaptive software, online learning systems, and communication technologies in overcoming barriers to participation. The study also explores the pedagogical and psychological mechanisms through which digital technologies enhance inclusive practices, such as fostering motivation, supporting differentiated instruction, and building collaborative learning communities. The opportunities for professional development of teachers in using digital resources are also considered, as the effectiveness of inclusive education heavily depends on educators’ digital literacy. Furthermore, the article discusses challenges related to infrastructure, teacher readiness, and accessibility of technological resources, while presenting strategies for their gradual resolution. By analyzing these dimensions, the study concludes that digital technologies play a pivotal role in shaping inclusive education, offering effective tools to meet the academic, social, and emotional needs of all learners.
Keywords: Inclusive education, digital technologies, assistive tools, accessibility, adaptive learning, teacher development, differentiated instruction, interactive platforms, collaboration, motivation